2019
DOI: 10.1002/johc.12089
|View full text |Cite
|
Sign up to set email alerts
|

Greening Counseling: Examining Multivariate Relationships Between Ecowellness and Holistic Wellness

Abstract: Researchers developed the ecowellness construct to draw focus on the human–nature connection in counseling. The authors examined relationships between the EcoWellness Inventory and the Five Factor Wellness Inventory in a study with 749 participants ages 18 to 84. Results provide further support for the significance of ecowellness as a dimension of holistic wellness that merits additional attention in humanistic counseling and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…After its initial conceptualization (Reese & Myers, 2012), the first author developed the EcoWellness Inventory, a 61-item instrument that addresses the respondent’s connection with nature relative to correlates of wellness (Reese, 2013). The model was empirically determined to include seven factors through confirmatory factor analysis (Reese, Myers, Lewis, & Willse, 2015), and multivariate analysis suggested that the model is intricately linked with the IS-Wel (Reese & Lewis, in press). We present the model and discuss it within the context of the multidisciplinary literature to provide a brief synopsis of the framework and relevant supporting literature. EcoWellness…one possible framework for strategically infusing nature throughout the school counseling curriculum…[is defined] as one’s sense of appreciation, respect for, and awe of nature resulting in greater feelings of connection to nature and holistic wellness .…”
Section: Ecowellnessmentioning
confidence: 99%
“…After its initial conceptualization (Reese & Myers, 2012), the first author developed the EcoWellness Inventory, a 61-item instrument that addresses the respondent’s connection with nature relative to correlates of wellness (Reese, 2013). The model was empirically determined to include seven factors through confirmatory factor analysis (Reese, Myers, Lewis, & Willse, 2015), and multivariate analysis suggested that the model is intricately linked with the IS-Wel (Reese & Lewis, in press). We present the model and discuss it within the context of the multidisciplinary literature to provide a brief synopsis of the framework and relevant supporting literature. EcoWellness…one possible framework for strategically infusing nature throughout the school counseling curriculum…[is defined] as one’s sense of appreciation, respect for, and awe of nature resulting in greater feelings of connection to nature and holistic wellness .…”
Section: Ecowellnessmentioning
confidence: 99%
“…The study reported in this article was one focus of a broader research effort in which we explored the factor structure of the EI (Reese et al, 2015) and initial validation of the assessment by examining relationships with hypothetically related constructs (Reese & Lewis, 2019). After receiving institutional review board approval, the first author recruited research participants through a secure registry of research volunteers in the United States called ResearchMatch (https://www.researchmatch.org/), which was established by academic institutions and the National Institutes of Health in the United States (Harris et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…They defined ecowellness as one's sense of appreciation, respect for, and awe of nature that results in greater feelings of connectedness and overall sense of wellness. Reese (2013) operationalized ecowellness through the development of the EcoWellness Inventory (EI), and Reese and Lewis (2019) recently identified multivariate relationships between the seven EI subscales and factors of the indivisible self model of wellness (IS‐Wel; Myers & Sweeney, 2008) through the Five Factor Wellness Inventory (Myers & Sweeney, 2005). They found that the ecowellness model was intricately related with the IS‐Wel, including one canonical function they labeled as “Indivisible Wellness.” Nearly every ecowellness factor was found to be related to the IS‐Wel, suggesting that the ecowellness construct is an integral component of wellness.…”
mentioning
confidence: 99%
“…Ecotherapeutic activities are examined within two categories: working in nature and experiencing nature. Working in nature includes various athletic activities defined as the green and blue gym [23][24][25][26][27][28][29], the most significant of which is walking [23][24][25][26][30][31][32][33][34][35]. Apart from athletics, this group comprises activities such as meditation/therapy [23,25,28,33,34,36,37], art [28,38,39], and production in/with nature (frequently gardening and horticulture) [36,38].…”
Section: Characteristics Of Ecotherapeutic Environmentmentioning
confidence: 99%